Reprogramming tumor microenvironment via systemic delivery of TLR3 agonist and manganese nanoparticle - Young Seok Cho; Xingwu Zhou; Xiaoqi Sun; Ziye Wan; Julia Crowther; Mariko Takahashi; Swetha Kodamasimham; Qi Wu; May Thazin Phoo; Youngseo Na; Kai Han; Zaiye Li; et al. (Proceedings of the National Academy of Sciences, 2025)
Toll-like receptor (TLR) agonists, as potent immunostimulatory adjuvants, play a critical role in linking the innate and adaptive immune responses. However, their antitumor effects as cancer immunotherapeutic agents have been limited. Here, we report our finding that manganese ion (Mn 2+ ) potentiates various TLR agonists, leading to robust activation of the TLR pathway and the stimulator of interferon genes (STING) pathway among innate immune cells. In particular, we have observed robust antitumor efficacy after intratumoral administration of a TLR3 agonist and Mn 2+ . To achieve systemic codelivery of TLR3 agonist and Mn 2+ , we have developed a low-molecular-weight poly(inosinic:cytidylic acid)-Mn 2+ coordination lipid nanoparticle (PLCMP). When administered intravenously in tumor-bearing mice, PLCMP successfully accumulated in tumor, induced innate immune activation, generated tumor-specific T cells, and exerted antitumor efficacy in TLR3- and STING-dependent manner without triggering overt toxicity. Moreover, PLCMP in combination with α-PD-1 therapy achieved long-lasting antitumor efficacy in multiple murine tumor models. Furthermore, vaccination with PLCMP carrying TC-1 tumor antigen peptide elicited strong antigen-specific CD8 + T cell responses and remodeled the tumor microenvironment, resulting in robust therapeutic efficacy. Overall, these results show that simultaneous activation of the TLR3 and STING pathways via PLCMP provides a promising strategy for immunotherapy and vaccination against cancer.